An Experimental Research Into the Bonding Strength of GFRP Bars in Concrete Under Elevated Temperatures - Ahmed Yahya Gaeeb; Muayad Mohammed Kassim (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study investigates the bond strength of Glass Fiber Reinforced Polymer (GFRP) bars in concrete at high temperatures. Twenty-four specimens were tested at 600°C to replicate fire conditions and analyze performance consequences in structural applications, with variables such as bar diameter and position within the concrete taken into account. The results show a considerable drop in binding strength, notably in edge-positioned bars with thinner covers, which is related to thermal degradation of the epoxy resin. The stress-slip relationship revealed significant increases in slippage, particularly for bigger diameter bars, as well as the vulnerability of GFRP bars to high temperatures. Failure modes shifted mostly to splitting following exposure, emphasizing the importance of design concerns in fire-prone structures. These findings improve our understanding of GFRP performance in harsh situations, influencing material selection for greater fire resilience.